Efficacy and safety of oral metronomic etoposide in adult patients with metastatic osteosarcoma. (25th November 2020) - Perret, Audrey; Dômont, Julien; Chamseddine, Ali N.; Dumont, Sarah N.; Verret, Benjamin; Briand, Sylvain; Court, Charles; Lazure, Thierry; Adam, Julien; Ngo, Carine; Even, Caroline; Levy, Antonin; et al.
Abstract: Therapeutic options in patients with metastatic osteosarcoma are limited and effective systemic treatments are needed in this setting. The aim of this case series was to assess the efficacy and toxicity of oral metronomic etoposide in adult patients with progressive metastatic osteosarcoma. We retrospectively reviewed the electronic records of patients treated with oral metronomic etoposide (25 mg thrice daily, 3 weeks out of 4) from December 2002 to December 2018 at Gustave Roussy (Villejuif, France). The primary endpoint was progression‐free rate (PFR) at 4 months; secondary endpoints were: best response (according to RECIST v1.1), progression‐free survival (PFS), overall survival (OS) and safety. With a median follow‐up of 9.8 months, 37 patients were eligible for this analysis: 68% males, median age 42 (range: 21–75), 19% with synchronous metastases, 92% with lung metastases, median PS: 1 (range: 0–3). Median number of previous treatment lines in the metastatic setting was 1 (range: 0–4). Progression‐free rate at 4 months was 40.3% (95% CI: 24.5–56.2). Best response was partial response in 11% and stable disease in 35% of patients (disease control rate: 46%). Median PFS was 3.1 months (95% CI: 2.5–4.7) and median OS was 9.8 months (95% CI: 5.1–12.3). Toxicity profile was acceptable, with 13% grade 3 haematological toxicities (anaemia and neutropenia), without any grade 3–4 non‐haematological toxicity. In our experience, oral metronomic etoposide demonstrated effective palliation along with acceptable toxicity in patients with progressive metastatic osteosarcoma. Abstract : Oral metronomic etoposide demonstrated effective palliation (progression‐free rate at 4 months was 40.3% (95%CI: 24.5‐56.2), along with acceptable toxicity in adult patients with metastatic osteosarcoma.